THE EVALUATION OF ENGLISH ELECTRONIC BOOKS FOR JUNIOR HIGH SCHOOL IN INDONESIA - Miftahul Rijal Anshar (Journal of English and Education, 2014)
This article reports the results of a study evaluating English Electronic Books for Junior High school in Indonesia. The study used Textbook Evaluation Checklist (Skierso 1991; Cunningworrth 1984), Focuses on physical Appearance, Content, and Supporting Aids of the textbook (Skierso 1991; Scott and Ytreberg, 1990; Grant, 1987; McGrath, 2002; Cunningworrth, 1984; Harmer, 2001; Woodward, 2001; Pinter, 2006) as a framework of text analysis. The study revealed that from several aspects both English Electronic Books (BSE) “Textbook 1 (T1)” and “Textbook 2 (T2)” fit the criteria of English textbooks in terms of physical appearance and content of the textbooks. However both textbooks need some improvement on how to design the activities and to add some proper supporting aids for the teacher. Both the textbooks are attractive in layout, and use some fun explanation on grammar and language function. They also emphasize listening and speaking skills. However the textbooks do not provide complete supporting aids for the teacher such as audio recording for listening activities and teachers’ book.